"Alcoholic" or "Person with alcohol use disorder"? Applying person-first diagnostic terminology in the clinical domain. Issue 1 (2nd January 2017) - Robinson, Sean M.
ABSTRACT: A recent publication by Broyles et al. has recommended extending the use of diagnostically accurate, person-first language (e.g., "person with alcohol use disorder") as an alternative to non-diagnostic, idiosyncratic terms (e.g., "addict", "alcoholic") when describing individuals with substance use disorders (SUDs) in academic publications. Given the high levels of stigma towards individuals with SUDs in both the public and professional community alike, however, the present commentary advocates for extending the use of appropriate terminology in the description of individuals with SUDs beyond the academic arena- i.e., clinical charting. The use of potentially stigmatizing idiomatic terms and descriptions (e.g., "clean", "dirty") in clinical charting is discussed with respect to: a) the lingering problem of the treatment utilization gap, b) modern conceptualizations of stigma and labelling among individuals with SUDs, as well as c) the emerging concept of structural stigma and how institutional standards (or lack thereof) may inadvertently contribute to the perpetuation of providers' negative attitudes and beliefs. The negative implications of SUD-related stigma on quality of patient care are also discussed, and possible barriers to the successful adoption of the above approach are considered. A number of possible benefits from the successful adoption of person-first, patient-centered, diagnostically appropriate labelling standards within clinical notes are hypothesized, including improved alignment with patient-centered care models, institutional values, and professional ethics, as well as reductions in institutional stigma. A number of recommendations to facilitate adoption of are offered.